Exercise-induced neuroplasticity: a new perspective on rehabilitation for chronic low back pain - Zou, Jianpeng; Hao, Shijie (Frontiers in Molecular Neuroscience, 2024)
Chronic low back pain patients often experience recurrent episodes due to various peripheral and central factors, leading to physical and mental impairments, affecting their daily life and work, and increasing the healthcare burden. With the continuous advancement of neuropathological research, changes in brain structure and function in chronic low back pain patients have been revealed. Neuroplasticity is an important mechanism of self-regulation in the brain and plays a key role in neural injury repair. Targeting neuroplasticity and regulating the central nervous system to improve functional impairments has become a research focus in rehabilitation medicine. Recent studies have shown that exercise can have beneficial effects on the body, such as improving cognition, combating depression, and enhancing athletic performance. Exercise-induced neuroplasticity may be a potential mechanism through which exercise affects the brain. This article systematically introduces the theory of exercise-induced neuroplasticity, explores the central effects mechanism of exercise on patients with chronic low back pain, and further looks forward to new directions in targeted neuroplasticity-based rehabilitation treatment for chronic low back pain.